THE RELATIONSHIP BETWEEN EMOTIONAL INTELLIGENCE AND LEARNING STRATEGIES ON STUDENTS' ACADEMIC ACHIEVEMENT - Sri Wahyudi (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2025)
This study aims to determine the relationship between emotional intelligence and learning strategies on students' academic achievement. Using a quantitative correlational approach, data was collected from 123 grade XI students at one of the State High Schools in Depok City through questionnaires and documentation of report card scores. The results showed that there was a positive and significant relationship between emotional intelligence and academic achievement (r = 0.482; p < 0.05), as well as between learning strategies and academic achievement (r = 0.533; p < 0.05). Multiple linear regression analysis showed that emotional intelligence and learning strategies simultaneously contributed 37.3% to the variation in students' academic achievement (R² = 0.373; p < 0.05). Learning strategies have a relatively greater influence than emotional intelligence. These findings indicate that students' academic success is not only influenced by intellectual ability, but is also highly determined by the management of emotions and the learning strategies applied. Therefore, effective education needs to integrate the development of emotional aspects and students' learning skills in a balanced manner to achieve optimal academic outcomes. This research provides an important basis for the development of more comprehensive guidance programs and learning strategies in schools.